Implementation of PHPUnit-Based Test Driven Development in PharmacyERP System Development - Cahyani, Silvia Dwi; Anggraeny, Fetty Tri; Nurlaili, Afina Lina (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2026)
This research applies the Test-Driven Development (TDD) methodology using PHPUnit to develop an ERP system for Apotek Pasyha using the Laravel 12 framework. Through a case study design and Red-GreenRefactor cycles, the development of eight core modules yielded 751 test cases and 2,146 assertions. System success was measured using the Test Pass Rate, achieving an "Excellent" category. Most modules reached a perfect pass rate, while technical constraints were only found in external libraries and rendering sequences rather than business logic. The results demonstrate that TDD is effective for SME-scale ERP development by enabling early defect detection, ensuring data accuracy, and producing functionally verified code to maintain the quality and reliability of complex systems.